semangat belajar di tengah keterbatasan analisis: bab 1 laskar pelangi - pairuz pairuz laksmiyati (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2026)
The phenomenal novel Laskar Pelangi by Andrea Hirata is a fictional story that portrays the reality of education in remote areas, touching on issues of social and economic injustice. This article specifically analyzes chapter 1, entitled Ten New Students, as the narrative and thematic foundation of the entire story. This opening chapter effectively presents the core conflict of the threat of closing to Muhammadiyah Elementary School (SD), the oldest school in Belitung, due to the minimum requirement of ten students. This analysis focuses on the dialogue between extreme limitations represented by the school's dilapidated physical condition and the students' poverty with a heroic and invincible spirit of learning. We will dissect how the dedication of educators, the miracle of the arrival of the tenth student, and the steely determination of children like Lintang, form an inspiring narrative that reaffirms that the essence of education is in hope and will, not in the luxury of facilities.